Present Status of Social Forestry in Punjab - Kapur, S. K. (Indian Forester, 1991)
Social Forestry In Punjab is becoming very popular. Large scale plantations of Eucalyptus are being raised under Social Forestry Programme. An Eucalyptus wood based factory of 80 TPD capacity for producing medium density fibre board la being aet up In the state. About 15 to 20 lac tonnes of surplus Eucalyptus pulpwood Is available annually from the private sector. Poplar planting Is also becoming popular.